2017
DOI: 10.1073/pnas.1613864114
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization dynamics and its scattering mechanism in thin CoFeB films with interfacial anisotropy

Abstract: Studies of magnetization dynamics have incessantly facilitated the discovery of fundamentally novel physical phenomena, making steady headway in the development of magnetic and spintronics devices. The dynamics can be induced and detected electrically, offering new functionalities in advanced electronics at the nanoscale. However, its scattering mechanism is still disputed. Understanding the mechanism in thin films is especially important, because most spintronics devices are made from stacks of multilayers wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 36 publications
5
45
0
Order By: Relevance
“…ratio a Considering the proportional correlation between the SOC and damping parameter, it is reasonable to define a damping term inter a that arises from the interfacial SOC. As also recently demonstrated by Okada et al [35], the interfacial PMA is found to be correlated with the Gilbert damping manifested by monitoring the ferromagnetic resonance linewidths with varying temperatures and sample thickness. According to the…”
Section: Resultssupporting
confidence: 73%
“…ratio a Considering the proportional correlation between the SOC and damping parameter, it is reasonable to define a damping term inter a that arises from the interfacial SOC. As also recently demonstrated by Okada et al [35], the interfacial PMA is found to be correlated with the Gilbert damping manifested by monitoring the ferromagnetic resonance linewidths with varying temperatures and sample thickness. According to the…”
Section: Resultssupporting
confidence: 73%
“…The Kerr angle θ Kerr is proportional to the ratio σ xy /σ xx by definition, and a large θ Kerr develops at Fe/insulator interfaces with decreasing σ xx and large σ xy . Our results show an efficient way to design novel devices, such as ultrathin ferromagnetic films 65 and ferromagnetic nanogranular films 66,67 by manipulating the substantial spin-orbit coupling effect at metal/insulator interfaces without using heavy elements.…”
Section: Resultsmentioning
confidence: 92%
“…Using out-of-plane FMR measurements, we determined the intrinsic damping by purposely suppressing the extrinsic contributions causing non-linear frequency dependence [16,17,44]. In practical applications, the relaxation mechanism for magnetization in the film-plane is of primary importance.…”
Section: Structure and Chemical Orderingmentioning
confidence: 99%
“…Still, reducing and tuning magnetic damping in metallic materials can be difficult due to magnon scattering by high density conduction electrons [10]. Notably, the lowest reported damping for CoFeB, the material employed by industry for MRAM development, is approximately 0.004 [16,17].…”
mentioning
confidence: 99%